Income inequality in disability-free life expectancy in Denmark. (13th November 2019) - Brønnum-Hansen, H; Foverskov, E; Andersen, I
Abstract: Background: The state old-age pension in Denmark is adjusted in line with the projected increasing life expectancy without taking social inequality in health and life expectancy into account. The purpose of the study was to estimate income disparities in life expectancy and disability-free life expectancy (DFLE) at age 50. Methods: By linking nationwide register data on income and mortality each individual at any age was divided into equivalised disposable income quartiles and life tables were constructed for each quartile. Data from the Danish Survey of Health, Ageing and Retirement in Europe (SHARE) was linked to register data providing access to information on respondents equivalised disposable income. Finally, data from the life tables were combined with prevalence on activity limitations by income quartiles from SHARE to estimate DFLE by Sullivan's method. Differences in DFLE were investigated and decomposed into contributions from mortality and disability effects. Results: A clear social gradient was seen for life expectancy as well as DFLE. Thus, life expectancy at age 50 differed between the highest and lowest income quartile by 8.0 years for men and 5.0 years for women. The difference in DFLE was 11.8 and 10.3 years for men and women, respectively. For men the mortality effect from the decomposition contributed by 4.1 years to the difference of 11.8 years in DFLE and 3.9 years to the difference in expected years with disability of 3.8 years while the disability effect contributed by 7.7 years. Conclusions: The study quantifies social inequality in health in Denmark. Although income inequality in life expectancy and DFLE can partly be explained by loss of income due to chronic diseases, one would expect a welfare state to provide better financial security for citizens with health problems. Furthermore, the marked social disparity when approaching retirement age is questioning the fairness of implementing a pension scheme independently of socioeconomic position. Key messages: Disability-free life expectancy differs between income quartiles by more than 10 years. Pension age follows the projected increasing life expectancy independently of socioeconomic position. This seems unfair.